Adopting composite geometric models for the heat conduction simulation of SiCp/Al matrix composites in the electrical discharge machining. (November 2020) - Chen, Jipeng; He, Guojian; Gu, Lin
Abstract: In the heat conduction simulations of electrical discharge machining, SiCp/Al composites are generally considered as homogeneous materials for simplification. This paper proposes that the composite geometric models containing SiC reinforcements could be built to improve the homogeneous material model. Three SiC particle equivalent shapes, circle, diamond, and triangle are selected and compared by conducting heat transfer simulations. The results demonstrated that the composite geometric model utilizing a circle SiC particle equivalent shape is better. This paper provides ideas and references for the modeling of composite materials in the heat transfer simulations of electrical discharge machining.